A very large antenna for the 1.8 MHz band. - Christman, Al
This article describes a large 1.8 MHz antenna system that generates significantly more forward gain than that produced by commonly-used phased-vertical arrays. It provides coverage of all four azimuthal quadrants, along with a choice of four elevation angles, which may be selected at the turn of a switch.
Keywords: Wire antennas; Phased arrays; Multi-beam antennas; Antenna radiation patterns; Mutual coupling